Differences in Physical Fitness, Learning Motivation, and Learning Outcomes of Physical Education Sports and Health Based on Student BMI - Adha, Arfa; S, Wedi; Gemaini, Andri; Lubis, Ade Evriansyah; Wahdi, Agung Hilmi; Syaputra, Aidil; Purwanto; Salsabilah; Diyanto, Rahmad (Journal of Sport and Exercise Science, 2025)
Purpose: This study compares differences in physical fitness (PF), learning motivation, and learning outcomes based on senior high school students' BMI (BMI). It examines students' PF across different BMI categories, the relationship between BMI and learning motivation, and Physical Education learning outcomes based on BMI. Materials and Methods: This study uses a quantitative approach of ex-post-facto type and comparative studies. The research population is 859 senior high school students. The sample was 95 students, who were selected using random cluster sampling and purposive random sampling techniques. The instruments used are TKJI, learning motivation scales, and grades. The data was analyzed using a multivariate statistical analysis of variance (MANOVA). Result: 1) There were differences in PF, learning motivation, and learning outcomes of students based on BMI (sig 0.000); 2) There is a difference in students' PF based on BMI (sig 0.000); 3) There was no difference in student learning motivation based on BMI (sig 0.867); 4) There is a difference in the learning outcomes of Physical Education students based on BMI (sig 0.000). Conclusion: This study found differences in PF and Physical Education learning outcomes based on BMI but not in learning motivation. The results highlight the need for tailored learning models, improved strategies, and a more decisive role for Physical Education in student well-being and learning quality.